Teacher Acceptance of Multimodality Digital Media in Mathematics Lessons with a Meaningful Learning Approach in Elementary Schools: Based on SUS - Nursidik, Ismail; Abidin, Yunus; Kurniawan, Dede Trie (International Conference on Elementary Education, 2025)
Digital technologies have changed the educational landscape, demanding a generation that is tech savvy, critical, creative and innovative. Mathematics, often considered difficult, requires an innovative approach. Multimodality digital learning media comes as a solution, supporting meaningful learning by linking new information to existing concepts. However, its utilization by teachers is still not optimal. This study aims to examine the acceptability of multimodality digital media in meaningful learning-based mathematics learning among 50 elementary school teachers in Lengkong Sub-district. Using quantitative survey method, data were collected through System Usability Scale (SUS) questionnaire, which assessed ease of learning, efficiency, memorability, error handling, and satisfaction. As a result, the media achieved an average SUS score of 76, placing it in the "Good" and "Acceptable" categories. This indicates a positive and significant acceptance from teachers. Nonetheless, this study was limited in terms of coverage area and number of respondents. For future studies, it is recommended to expand the coverage and respondents for more representative results. In conclusion, this media has great potential to create more interesting and meaningful math learning.